Formation Mechanism and Sustainable Utilization of Ningwu Ice Cave in China - Yang, Shaohua; Shi, Yaolin (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 4, 2023)
The present study investigated the energy exchange of Ningwu Ice Cave and then quantitatively interprets the formation and preservation mechanism of the ice deposit. Heat energy is conducted inefficiently into the ice cave from outside and wall rock in spring, summer, and autumn. While in winter, heat energy is transferred very efficiently due to the air natural convection, thus cooling it down. Wherever the annual average air temperature is higher than 0 °C, ice caves can be found. The largest ice cave in China, Ningwu Ice Cave in Shanxi Province, serves as an illustration. We simulate the heat transfer process at this ice cave using the Finite Element Method in order to quantitatively investigate the mechanism of formation and preservation of the ice cave. The calculation aids in assessing the effects of global warming, tourists, coloured lights, climatic conditions, and other factors on the long-term development of the ice cave as a tourism resource. Other ice caves in China had airtight doors installed at the entrances in an effort to "protect" them, but this prevented cooling in the winter, and the ice in these caves will completely melt within tens of years. Rare natural landscapes typically have a very high value in terms of utilization. The benefit extends beyond science to include economics. Like ice caves, particularly those found in temperate regions like Ningwu Ice Cave. On the one hand, ice bodies can be used to study small-scale climate changes over the past few decades. On the other hand, on the basis of scientific protection and development, ice caves can be opened to tourists as a tourism resource to promote the development of the local tourism market and drive the development of green economy with local characteristics. Details of sustainable utilization of Ningwu Ice Cave in China were analyzed.